British North America : B. Bay, C. Cape, F. Fort, H. Harbour, Ho. House, L. Lake, M. Mountain, P. Port, Pt. Point, R. River. - Society for the Diffusion of Useful Knowledge (Producer); J. & C. Walker (Firm) (Contributor)
Map of British North America, including territorial divisions, names of lakes, rivers, and locales, contours, and random details such as coal veins, factories, and trading posts. "Hudson Bay Comp. M.S.S. Parry, Franklin, Beechey, Graab, &c." Scale 1:15,500,000 or 69.3 English Miles=1 Degree. Lake Nippising looks like a ghoul. Also depicts Mexico, United States, Columbia, Russian America, Greenland, and Iceland. [Originially published : Maps of the Society for the Diffusion of Useful Knowledge. Vol. 1. London: Chapman and Hall, 186, Strand, 1844.] Depressions shown by hachures. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .